HOW MALL HELPS MAJORED STUDENTS PROMOTE THEIR LEARNER AUTONOMY THROUGH OUT-OF CLASS ACTIVITIES AT VĂN LANG UNIVERSITY - Linh, Trần Thị Ngọc; Lê, Trương Bạch; Tín, Đặng Tấn (International Journal of Psychosocial Rehabilitation, 2020)
The rapid development of high technologies has brought EFL/ ESL teachers all over the world a lot of opportunities to experience new devices and applications which help educators or trainers improve their old existing teaching methodologies (Grammar-Translation Method, Direct Method, Audio-Lingual or Total Physical Response) and construct suitable ways such as using MALL because “The future is increasingly mobile, and it behoves us to reflect this in our teaching practice” as noted by Hockly (2013), known as a move approach to help both EFL/ ESL teachers and learners achieve benefits with positive reactions in their language practices that have been largely recorded for ages. This research paper, therefore, aims at presenting how MALL can help students to develop their learner autonomy at Van Lang University in Vietnam. The study was conducted within ten weeks with the participation of ninety-seven English majors in two academic classes at the pre-intermediate level. The data was collected with means of questionnaire, observation, interviews, and students’learning diaries. The findings indicated that the assistance of mobile devices associated with the platform “Google-classroom” known as a social networking learning management system engaged both social interaction and collaboration of students closely for outside class activities, and also depicted that their learner autonomy was significantly improved with amazing results including the awareness of students towards English practices outside the class increasingly, students’ readiness towards giving their feedback or reflection to the work of their classmates after class positively, the development of EFL learners’ confidence clearly, and so on. Nevertheless, some external and internal issues need to be examined carefully for better future research such as the lack of students’ technical expertise, learners’ different language learning styles, the lack of learners’ motivation, limited internet connection, costs for internet use, and the limitation of students’ communicative or collaborative skills.Tran Thi Ngoc Linh has been teaching English for tertiary students with more than 15 years. Her lectures include English for Tourism, English for Hospitality, English for Translation and Interpretation, English for Business Administration, English for Marketing, English for Teaching Methodology, Academic Skills, and Basic Skills in English. She has mostly worked for universities in the South of Vietnam such as School of Hospitality Management (VATC), HUTECH University, BinhDương University, HCMC University of Pedagogy, HongBang International University, and VanLang University. She has already graduated her MA degree in TESOL from Victoria University of Australia and an MBA degree from Open University of Malaysia. She has also been conducting her PhD study in TESOL at Hue University of Foreign Languages, Hue University, Vietnam. Her current research interests include areas of MALL, Learner autonomy, and ELT.